2015
DOI: 10.18561/2179-5746/biotaamazonia.v5n3p50-54
|View full text |Cite
|
Sign up to set email alerts
|

Dieta Natural de Macrodon ancylodon (Bloch & Schneider, 1801) Capturada por Embarcações Pesqueiras Industriais Sediadas no Estado do Pará

Abstract: Os espécimes de Macrodon ancylodon foram coletados no período de dezembro de 2010 a novembro de 2011, da costa do Amapá ao litoral do Pará, utilizando duas redes de arrasto simultaneamente para peixes e camarão, e realizadas seis amostragens diárias com duração média de 2h. Em laboratório os estômagos de M. ancylodon foram fixados em formalina à 4 %, retirados para pesagem e análise dos itens alimentares, sendo calculado a Frequência de Ocorrência (Fi), Índice de Análise Volumétrica (Vi), Índice de Importância… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Three groups have already been found in the M. ancylodon diet: shrimp, fish and molluscs (Figueiredo 2014). Castro et al (2015) showed that, in M. ancylodon collected by fishing vessels in the state of Pará -Brazil, the items that presented the highest frequency of occurrence and food importance index were the shrimp fragments, fish fragments, Penaeidae and Polychaetas, showing a basically carnivorous diet. Magro et al (2000) have already demonstrated that the diet of M. ancylodon depends on its degree of growth, varying throughout its life, with a decrease in the preference for crustaceans and an increase in fish consumption, the latter being directly proportional to the growth of the specimen.…”
Section: Discussionmentioning
confidence: 98%
“…Three groups have already been found in the M. ancylodon diet: shrimp, fish and molluscs (Figueiredo 2014). Castro et al (2015) showed that, in M. ancylodon collected by fishing vessels in the state of Pará -Brazil, the items that presented the highest frequency of occurrence and food importance index were the shrimp fragments, fish fragments, Penaeidae and Polychaetas, showing a basically carnivorous diet. Magro et al (2000) have already demonstrated that the diet of M. ancylodon depends on its degree of growth, varying throughout its life, with a decrease in the preference for crustaceans and an increase in fish consumption, the latter being directly proportional to the growth of the specimen.…”
Section: Discussionmentioning
confidence: 98%
“…The methodology used in the analysis of the feeding habits of P. brasiliensis in the South Atlantic of Brazil was adequate, as in several studies involving natural fish feeding (Branco et al, 2005;Machado et al, 2014;Castro et al, 2015), although the recognition of prey was restricted to large groups. However, as suggested by Branco and Verani (1997), the most important is to determine the food spectrum of the species and the relation among them.…”
Section: Discussionmentioning
confidence: 99%
“…The calculated variables (% FO, % PM and % IAi) quantify the importance of each item in the diet of the species under study, considering the volume occupied in the stomach and the amount of different food items (Castro et al, 2015). With this method, we estimate the food preference of the species Paralonchurus brasiliensis.…”
Section: Diet Descriptionmentioning
confidence: 99%
“…The distribution of M. ancylodon is restricted to the western part of the Atlantic Ocean, from Venezuela to Argentina (Cervigón 1993, Carvalho-Filho 1999. It is a demersal species found in estuarine and marine habitats of tropical and subtropical regions at depths of up to 60 m (Camargo & Isaac 2005, Castro et al 2015. It is characterized by an elongated, yellowish/grayish body, up to 45 cm in length, moderately compressed with arched dorsal and ventral fins (Santos et al 2006).…”
Section: Introductionmentioning
confidence: 99%